Formes de l`interdisciplinarité et configuration de quatre Centres de recherche en sciences du sport en Europe - Fargier, P.; Camy, J.; Champely, S.; Belli, A.; Perrin, C. (Movement & Sport Sciences - Science & Motricité, 2016)
Interdisciplinarity is often considered as a constitutive element of Sport Science, while the implementation of interdisciplinary research in this area remains to be characterized. With this aim, the present study examined four European Research Centres in Sport Science claiming an interdisciplinary development. A lexical analysis of the interviews of the persons in charge of the Centres was combined with an intuitive classification of the overall informations collected about the functioning of these Centres. This led to the determination of four dimensions or « forms » (the « academic », « scientific », « organisational » and « societal » forms). The examination of the interaction of each form with the others led to design specific configurations of the Centres while in each case the organisational form and the societal form appeared to play a key role in the setting of sustainable interdisciplinary activities. In this framework, the main supports resides in the creation among researchers of a common culture and strong interest for the other scientific disciplines than their own and a capacity to secure long term financing dedicated to interdisciplinary research.